Contribution des residus de recoltes au disponible fourrager de saison seche dans la plaine d'Abet (Nigeria central) - Powell, J.M. (1985)
Discusses the contribution of crop residues to livestock feed resources during the dry season in the Abet plains, central Nigeria. Determines the grain and vegetative dry matter yields of predominant crops and the relationship between the two; percentage composition of crop residues; fiber, silica content and apparent digestibility of crop residue plant parts; and the quality of total crop residues.